2021
DOI: 10.1021/acs.jcim.1c00263
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Ability of Common Docking Programs to Correctly Reproduce and Score Binding Modes in SARS-CoV-2 Protease Mpro

Abstract: The coronavirus SARS-CoV-2 main protease, M pro , is conserved among coronaviruses with no human homolog and has therefore attracted significant attention as an enzyme drug target for COVID-19. The number of studies targeting M pro for in silico screening has grown rapidly, and it would be of great interest to know in advance how well docking methods can reproduce the correct ligand binding modes and rank these correctly. Clearly, current attempts at designing drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 106 publications
(209 reference statements)
3
54
0
Order By: Relevance
“…We have found that in about ' 35% of these 28 structures Vina is able to identify the correct (crystallographic) binding pose with a tolerance of less than 3 Å RMSD, and in ' 70% of the cases the crystallographic binding mode was found among the poses within 0.3 kcal/mol of the best scoring pose. As observed in Ref., [ 38 ], Vina performances tend to improve for bulky ligands such as PF-07321332. Full results of this analysis can be found in the ESI.…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…We have found that in about ' 35% of these 28 structures Vina is able to identify the correct (crystallographic) binding pose with a tolerance of less than 3 Å RMSD, and in ' 70% of the cases the crystallographic binding mode was found among the poses within 0.3 kcal/mol of the best scoring pose. As observed in Ref., [ 38 ], Vina performances tend to improve for bulky ligands such as PF-07321332. Full results of this analysis can be found in the ESI.…”
Section: Methodssupporting
confidence: 60%
“…Vina is known to improve the average accuracy of the (non covalent) binding mode predictions on the well established DUD-E benchmark set [ 37 ] of more than 50% compared to AutoDock4, and it was found to be a strong competitor against popular commercial programs, resulting at the top of the pack in many cases. In a recent paper [ 38 ], the ability to correctly reproduce the binding modes in SARS-CoV-2 3CL pro of popular docking programs, including Vina, was questioned. In this study [ 38 ], 85 co-crystal 3CL pro structures with non-covalently bound ligands were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Are there experimentally determined values of affinity to compare to? Perhaps we can hope that docking will at least give us a reliable docking pose: sadly, for the case of mPro in SARS-CoV-2, this has been shown not to be the case [22], so even more care needs to be applied when using docking as a positive filter rather than a negative one.…”
Section: Scoring Methodsmentioning
confidence: 99%
“…Combined with extensive next generation sequencing, it will guide drug discovery and help understand the biological significance of amino acid variations, in particular in the context of a viral pandemic. Advanced computational and machine learning methods should also help improve the performance of in silico docking programs, whose limitations have been highlighted by the COVID-19 pandemic [ 155 ].…”
Section: Virus- and Host-targeted Therapies Vaccine Developmentmentioning
confidence: 99%